VSEIR Mathematical Model on Anthrax Disease Dissemination in Animal Population with Vaccination and Treatment Effect - Nurfitria Prawandani Asikin (Department of Mathematics, Hasanuddin University, 2020)
AbstractThis research aimed to determine the equilibrium point and analyze the stability of VSEIR model on Anthrax Disease with vaccination and treatment effects. It also aimed at measuring the level sensitivity of Anthrax disease deployment to proportion vaccination effect and proportion treatment effect by using . The writer used qualitative method to achieve the above objectives. The steps were: Reproduction Base Numbers, The R0, was analyzed using stability of disease-free equilibrium points, where the equilibrium point of both is said to asymptotically stable if and unstable if that originally based on the next generation method. Next, the writer also analyze the stability of equilibrium point that was obtained by using the Routh-Hurwitz Criteria and Numeric Simulation. After analyze the sensitivity, the writer finds the proportion of vaccination effects on new-born animal and the treatment of infected animal can reduce the spread of Anthrax Virus and also to terminate the endemic conditions. The numeric simulation is involved to describe the level of vaccination effect new-born animal, and the treatment of infected animal at Anthrax disease deployment.